PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ulfa Hanifah, - (2019)
This study aims to determine the effect of Profitability proxied with Return On Equity (ROE), Firm Growth proxied by Asset Growth (AG), and Capital Structure proxied by Debt to Equity Ratio (DER) toward Firm Value proxied by Price to Book Value (PBV). Population in this study are consumer goods companies listed in Indonesia Stock Exchange (IDX) 2014-2017. The technique of determination of the sample using the method of purposive sampling and obtained 49 consumer goods companies with a research period of four years to obtain 26 units of samples. Data analysis was done using Microsoft Excel 2016 and hypothesis testing in this research using Data Panel Regression Analysis with EViews 10.0 program and significance level of 5%. The result of the research shows that (1) profitability (ROE) has a significant positive effect on firm value (PBV), (2) firm growth (AG) no significant effect on firm value (PBV), (3) capital structure (DER) has significant positive effect on firm value (PBV).